A study on organizational culture in the brazilian cosmetics sector - Romano, André Luiz; Teixeira, Isabela Tatiana; Alves Filho, Alceu Gomes; Helleno, André Luís (Revista de Administração da UFSM, 2019)
The concept of culture can be defined as the way in which things are done in a particular environment, ranging from a house, even a country, through the various actors involved in relationships. To address the issue in companies, there is the so-called organizational culture. In organizations culture is influenced by issues such as power, hierarchy and conservatism. The research presents the results of the assessment of organizational culture in the Brazilian cosmetic industry, through the analysis of segmentation and matching. The analyzes show that the overall profile of culture in these companies is hard, with influence based on position, prioritization of individual aspects, and traditionally masculine values. The correspondence analysis showed that British companies and with possession of more than 500 employees are associated with those, more flexibility in the culture, not the existence of different privileges to different levels, the prioritization of the group over the individual, employee access to directors is common, and not the presence of divisions of roles linked to gender. Chinese and Japanese national companies are associated with companies with clear division of roles between men and women and companies with no analytical thinking.